Algoritmo híbrido aplicado ao planejamento da expansão de redes aéreas de média tensão - Cuno, Miguel Angel Sánchez (2016)
This work presents the development of a Hybrid Algorithm to solve the problem of Planning the Expansion of Medium Voltage Overhead Networks. The Hybrid Algorithm uses two strategies to solve the problem. First uses a Constructive Heuristic Algorithm that tries to work with parameters instead of working with variables, with the objective of reducing the convergence time to the research process trying not to impair the quality of the solution. The second strategy is based in a Branch and Bound Algorithm, that uses the solution of the problem obtained as a starting point while the first strategy is running. Thus, this solution is used like incumbent in the second process. In this context the hybrid algorithm developed and implemented in this work, takes advantage of reducing the convergence time of the Constructive Heuristic Algorithm and the advantage of guarantee that the solution has the best quality, which are the solutions produced by algorithms type Branch and Bound. The Algorithm has been tested in three test systems, being established a plan to expand overhead medium voltage networks for each system.